2022
DOI: 10.1371/journal.pone.0273155
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic elite strategy mayfly algorithm

Abstract: The mayfly algorithm (MA), as a newly proposed intelligent optimization algorithm, is found that easy to fall into the local optimum and slow convergence speed. To address this, an improved mayfly algorithm based on dynamic elite strategy (DESMA) is proposed in this paper. Specifically, it first determines the specific space near the best mayfly in the current population, and dynamically sets the search radius. Then generating a certain number of elite mayflies within this range. Finally, the best one among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…The majority of the ideal male mayfly individuals will, however, be concentrated close to the global optimal solution in the later stages of the algorithm, falling into the local optimal solution. To solve this, Qianhang Du and Honghao Zhu [32], presented an enhanced Mayfly Algorithm Based on Dynamic Elite Strategy (DESMA), which begins with the global optimal solution and executes a more precise elite selection strategy in proximity to the global optimal solution, to address the aforementioned issues. The algorithm can, on the one hand, break out of the local optimum, increase population diversity, broaden the search space, and potentially discover a new global optimal solution that outperforms the optimal global solution from the previous generation; on the other hand, when maintaining population integrity, it not only increases convergence accuracy but also speeds up convergence and finds the optimal global solution more steadily.…”
Section: Dynamic Elite Strategy Mayfly Algorithmmentioning
confidence: 99%
“…The majority of the ideal male mayfly individuals will, however, be concentrated close to the global optimal solution in the later stages of the algorithm, falling into the local optimal solution. To solve this, Qianhang Du and Honghao Zhu [32], presented an enhanced Mayfly Algorithm Based on Dynamic Elite Strategy (DESMA), which begins with the global optimal solution and executes a more precise elite selection strategy in proximity to the global optimal solution, to address the aforementioned issues. The algorithm can, on the one hand, break out of the local optimum, increase population diversity, broaden the search space, and potentially discover a new global optimal solution that outperforms the optimal global solution from the previous generation; on the other hand, when maintaining population integrity, it not only increases convergence accuracy but also speeds up convergence and finds the optimal global solution more steadily.…”
Section: Dynamic Elite Strategy Mayfly Algorithmmentioning
confidence: 99%
“…Previous studies have fully demonstrated the superiority of metaheuristic optimization algorithms in solving large-scale search and optimization problems [ 23 ]. In the last year of research, the slime mold algorithm has fully demonstrated its applicability in engineering optimization problems as a new meta-heuristic optimization method.…”
Section: Related Workmentioning
confidence: 99%
“…This idea has been transformed into an optimization technique known as the MA. The algorithm is constructed by integrating elements from firefly algorithm (FA), particle swarm optimization (PSO) and genetic algorithms (GA) [18][19][20]. By incorporating the strengths of each of these approaches, the MA algorithm was devised.…”
Section: Introductionmentioning
confidence: 99%